Response of free-living Nematodes to the quality of water and sediment at Bou Chrara Lagoon (Tunisia) during winter 2000 - MAHMOUDI, E.; BEYREM, H.; BACCAR, L.; AISSA, P. (Mediterranean Marine Science, 2002)
The Bou Ghrara lagoon, a stretch of water in southeastern Tunisia, has shown an alarming reduction of its fishery resources since 1993. In order to study the response of free-living nematodes to the water and sediment quality of this area, thirteen stations have been sampled. According to this study, the heavy metal, organic carbon and hydrocarbon content of sediments are key factors negatively influencing the density, biomass and diversity of the nematofauna.